If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 44) + (-10x + 65) = 180 Reorder the terms: (44 + 6x) + (-10x + 65) = 180 Remove parenthesis around (44 + 6x) 44 + 6x + (-10x + 65) = 180 Reorder the terms: 44 + 6x + (65 + -10x) = 180 Remove parenthesis around (65 + -10x) 44 + 6x + 65 + -10x = 180 Reorder the terms: 44 + 65 + 6x + -10x = 180 Combine like terms: 44 + 65 = 109 109 + 6x + -10x = 180 Combine like terms: 6x + -10x = -4x 109 + -4x = 180 Solving 109 + -4x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-109' to each side of the equation. 109 + -109 + -4x = 180 + -109 Combine like terms: 109 + -109 = 0 0 + -4x = 180 + -109 -4x = 180 + -109 Combine like terms: 180 + -109 = 71 -4x = 71 Divide each side by '-4'. x = -17.75 Simplifying x = -17.75
| 5x^(3/2)-25x^(1/2)+30x^(-1/2) | | 35x^6/7x^(1/4) | | 11+(-6)(3)= | | 3x+9=5x+10 | | 7x-10/4=-6 | | 0=2v-8 | | 22/2+(-6)(3) | | 5295/4.13 | | 8=-w+14 | | 7x-10/4=6 | | 3x-12x=4x+7x-16 | | 3(2z-7)=5z+17+2 | | 3x+4x-6=2 | | (22x+253)/30=11 | | (X/4)=23 | | c/2+3=-2 | | 18+x=51 | | 3y^2+15y=42 | | c/2+3-3=-2-3 | | 15y-14y+5=6 | | 5x-11=9-(4-14) | | 2r^3-3r^2=32r-48 | | 4x-9=24-3 | | 3/5x-10=-1 | | 4x-6(2x+3)=-2 | | 18.9=23.9 | | 36/60=45/x | | 37=32-2c | | 13.78-.8a=0 | | 16=8(x-1)-8 | | x/7-5/4=x/14-1/28 | | 19z-18z=16+22 |